Understanding the Eastern Mediterranean Policy of France and Recent Tensions with Turkey - Örmeci, Ozan (UPA Strategic Affairs, 2021)
Abstract: As one of the ancient powers of the Mediterranean, France has been implementing active policies in recent years in response to geopolitical developments in the Eastern Mediterranean region under Emmanuel Macron’s Presidency (2017-). These policies recently caused some political problems between France and Turkey. In this piece, main elements of French policy towards Eastern Mediterranean will be analyzed and issues that cause competition between France and Turkey will be revealed.
Keywords: Eastern Mediterranean; French Foreign Policy; Turkish Foreign Policy; FrenchTurkish Relations; Emmanuel Macron